Countering Terror Cells: Offence Versus Defence. Issue 3 (3rd April 2021) - Bhan, Aditya; Kabiraj, Tarun
ABSTRACT: The analysis provides insights regarding the suitability of offensive versus defensive measures in countering a terror cell. It is shown that the optimal resource allocation is more offensive when the cell is aware of which targets have been protected, but does not distinguish between the values of different targets; than the case where it neither distinguishes between target values nor is the protection conspicuous. Also, the ability of the terror cell to inflict damage is least when it neither distinguishes between target values nor is the target protection conspicuous, and most when it shares the counter-terrorists' target valuations and observes target protection. Hence, from the counter-terrorism (CT) point of view, there seems to be a rationale in making CT target valuations and target protection inconspicuous to the extent possible. The paper finally deals with the possibility of diverging target valuations from the CT standpoint and that of the terror cell and shows that if target protection is conspicuous to the cell and these are common knowledge, then the optimal CT allocation is at least as offensive as the case with identical valuation rankings.